Study Planning of Additional Roughness Layer Thick (Overlay) at Sections of The Road Tokoluli - Gleno (Sta.40+000âSta.45+000) Timor Leste - Exposto, Lino De Jesus Madeira; Rahma, Pamela Dinar; Arifianto, Andy Kristafi (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2018)
ABSTRACT The way this is Tokoluli - Gleno a path that connects the District with the Capital of Ermera. The street was included in the classification of the arterial road (national road) that is the way in which the vehicle is going through quite a lot and has a heavy load. Because it is often traversed by vehicles that burdened the road conditions lead to be broken, so the road needs to be fixed or in rehabilitation of rework. Based on the existing conditions in what the study, the planning of additional roughness layer thick (overlay) at sections of the road from Tokoluli - Gleno (sta.40+000âsta.45+000) Timor Leste This is intended to bolster the pace of economic growth with the increasing needs of the means of transport that can launch a transport in the area and the development of the quality or quantity of the vehicle linking it with the capital of Ermera Regency Country. In this study, the authors will discuss the planning process calculation of thick layers of additional roughness (overlay) on road improvement project Tokoluli - Gleno. explaining the methods performed in the planning of additional roughness layer thick (overlay). The methods used in this study is a method of Bina Marga can get thick arrangement of roughness consists of the Foundation of the bottom (Sub Base) thick 8 cm with an aggregate class B, the Foundation top (Base Course) thick 20 cm with an aggregate class A, surface layer (Surface) 5 cm surface layer (Laston). The final project report is expected to be of benefit to the author himself to add science in calculating the thick layers of additional roughness (overlay) of these, so expect roads planning able to spur the economy in the regions of pertumnbuhan and future welfare of society can be raised. Keywords ; thick layers ; additional roughness (overlay) ; timor leste.